In vitro synergy of natamycin and voriconazole against clinical isolates of Fusarium, Candida, Aspergillus and Curvularia spp. Issue 1 (5th October 2017) - Sradhanjali, Swatishree; Yein, Bandana; Sharma, Savitri; Das, Sujata
Abstract : Aim: To determine the minimum inhibitory concentrations (MICs) of voriconazole and natamycin, alone and in combination, against the clinical isolates of Fungus and to evaluate the synergy between the drugs in an experimental in vitro study. Methods: In an experimental in vitro study, clinical isolates of Fusarium, Aspergillus, Candida and Curvularia spp were maintained on Sabouraud Dextrose Agar and used for the study. The MICs of natamycin and voriconazole, used alone and in combination, were evaluated by checkerboard microdilution technique based on the standard protocol proposed by the Clinical Laboratory Standards Institute. The interactions were assessed using the fractional inhibitory concentration (FIC) Index model. Results: Tested with all the clinical isolates, the MICs ranged between 0.125 and 8 µg/mL both for natamycin and voriconazole. In descending order, maximum synergism (FIC ≤0.5) was observed in Candida spp (33.3%) followed by Curvularia spp and Fusarium spp (23.1%). Synergism was least for Aspergillus spp (22.2%). However, at 61.5% (8/13), maximum additive effect (>0.5–1) was observed in Aspergillus spp and minimum (33.3%, 2/6) in Candida spp. Indifference (FIC value >1 and≤4) was observed in 22.2% (2/9) of Aspergillus spp, 15.4% (2/13) of Fusarium spp, 33.3% (2/6) of Candida spp and 23.1% (3/13) of Curvularia spp. No cases of antagonism (FIC >4) were observed. Conclusions: Natamycin and voriconazole in combination demonstrated more effective antifungal activity than single-use in vitro treatment in all species tested, which implies that these combinations may be helpful in treating fungal keratitis. There was no antagonism between these two drugs.